Penerapan Model EPIC Short Film “Tenang” terhadap Brand Awareness Kanal YouTube Yura Yunita - Lisdayanti, Annisa; Hapsari, Ayuningtyas Yuli (https://jurnal.binamandiri.ac.id/, 2023)
The rapid development of digital technology has had a significant impact on various aspects of life in Indonesia. One of the websites frequently visited by Indonesian people is YouTube, where this platform offers a wide variety of video content that can be enjoyed by the public. Currently, an increasing number of music videos in the form of short movies or short films are uploaded to YouTube. In line with this reason, one Indonesian singer who shares a short film as one of her music videos is Yura Yunita. The short film, released on November 29, 2018, on Yura Yunita's YouTube channel, has been viewed by up to 2.2 billion viewers as of March 6, 2023. Enhancing the effectiveness of content based on the communication impact generated will increase the number of subscribers to the YouTube channel. Research results show that the Model EPIC in the short film content